EDUKASI UPAYA MEMPERTAHANKAN KUALITAS HIDUP PADA MASA PANDEMI COVID 19 - lilik sriwiyati; Endang Dwi Ningsih; Warsini (Abdimas Kosala : Jurnal Pengabdian kepada Masyarakat, 2022)
The number of Covid-19 cases and/or the number of death have increased, it has an impact on the political, economic, social, cultural, defense and security aspects, and also the welfare of the people in Indonesia. Pandemic conditions will cause the people feel worry and depressed. Various impacts experienced by the community will cause problems both from an economic and psychological perspective that can affect the quality of life. Quality of life is a person's quality of life based on a person's subjective assessment of himself. During the Covid-19 pandemic, people's quality of life must be maintained. People must be able to carry out various kinds of activities to achieve an optimal quality of life. Efforts is needed to achieve an optimal quality of life, one of which is through education about efforts to maintain the quality of life during the Covid 19 pandemic. This activity aims to increase community knowledge in Lawu Nguter Sukoharjo about efforts to maintain quality of life during Covid-19 pandemic. Keywords: Covid-19, education, quality of life